Penyuluhan Hukum Tentang Relevansi Qanun Aceh dengan Pembangunan Karakter Generasi Z di SMK 4 Lhokseumawe - Aksa, Fauzah Nur; Jafar, Sofyan; Al Fikri, Albert; S, Sumiadi; A, Arnita; F, Fatahillah; Subaidi, Joelman (Yayasan Daarul Huda Kruengmane, 2024)
Generation Z interaction with digital devices and the internet is very high. The latest data from March 2023 published by Populix Co-Founder and CEO Dr. Toimothy Astandu states that Indonesians spend an average of 8-10 hours per day using mobile phones. This data is higher than the 2022 data published in the State of Mobile report which recorded a figure of 5.7 hours per day in the use of mobile phones. This will result in a lack of sensitivity, attention deficit disorder, and difficulty building interpersonal relationships. In addition, their understanding of legal norms and values, which can help them to form good character and akhlakul karimah is relatively low. To respond to these problems, Malikussaleh University Faculty of Law lecturers have conducted legal counselling on the Relevance of Qanun Aceh to Generation Z Character Building at SMK 4 Lhokseumawe. This activity is a form of Tridarma Perguruan Tinggi where each lecturer carries out community service to help provide solutions that occur in society.